Amalan Makna Persaudaraan sebagai Nilai Kemanusiaan Buddhisme demi Keutuhan Bangsa - Wiliem Lesmana; Rustono Farady Marta; Sulaiman Girivirya (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
In the midst of Indonesian society which is full of diversity, so there needs to be a sense of tolerance and respect for these differences in order to maintain the integrity of the nation, where this is in line with Buddhist teachings which also teach to be able to live in people’s lives so that the desired state of peace and prosperity will emerge. communicate as stated in the text of the 2020 Vesak message of Sa?gha Therav?da Indonesia is reviewed through the use of Buddhist communication theory as part of communication theory originating from the east and Buddhist semiotics to dissect the meaning of the text so that it can be practiced in daily life. The findings from the analysis of the text show that each paragraph in the text of the 2020 Vesak message of Sa?gha Therav?da Indonesia has a Buddhist-based communication delivery pattern that is beneficial not only for Buddhists but for the wider community about the importance of practicing the teachings of love in building a spirit of fraternity in order to maintain the integrity of the Indonesian nation.